Determinan Pengungkap Akuntansi Sumber Daya Manusia dalam Perusahaan Manufaktur di Bursaf Efek Indonesiah - Anggun Putri Dewi; Putra, Danang Adi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to ascertain how firm size, profitability, and institutional ownership relate to accounting disclosures related to human resources. The reason this variable was selected is that it is one of the factors that affects disclosure of human resources. This study tests hypotheses using quantitative research methods. The business data used in this study's secondary data comes from the 2022 annual reports of manufacturing firms in the basic industrial and chemical sectors that are listed on the Indonesia Stock Exchange The author employed a purposive sample methodology, which is a sampling strategy that is based on predetermined criteria. Thirty data study samples were employed, all of which were selected according to predefined criteria. This study's data analysis method makes use of multiple linear regression. The study's findings demonstrate that human resource accounting disclosures are positively impacted by a company's size. Disclosures in human resource accounting are influenced by profitability. Accounting disclosures pertaining to human resources benefit from institutional ownership.